Review: Biomass-Based Hydrogen Production Technology - Jamilatun, Siti; Muhtadin, Akhmad Sabilal; Nurmustaqimaha, Nurmustaqimaha (Universitas Ahmad Dahlan, 2023)
One of the most efficient fuels for renewable energy is hydrogen. Currently, fossil fuels and their by-products produce most of the hydrogen with technologies that harm the environment, and fossil sources are rapidly decreasing in quantity. Environmentally friendly and pollution-free alternatives to fossil fuels are interesting to pursue. This paper explores advances in bio-hydrogen technology as an environmentally friendly and sustainable future technology development. Derivatives of crucial products from biomass, such as alcohol and glycerol, and methane-based reforming to produce hydrogen. Biological techniques to produce bio-hydrogen are exciting by fermentative, enzymatic, and biocatalytic methods. Also discussed are genetic engineering components, reactor configuration, and pretreatment. Low hydrogen yield and high cost are the two main problems in bio-hydrogen production. Also discussed are the costs, advantages, and disadvantages of various hydrogen generation methods. This article also discusses the promise of biohydrogen as a clean energy alternative and areas that require further research